An Elegy to Courtly Love: Rewriting and Reconstructing the Tradition of Courtly Love in Chaucer’s Works - Wu, Hongrong (International Theory and Practice in Humanities and Social Sciences, 2025)
As the first great poet to write in English in the history of English literature, Geoffrey Chaucer is honored as the “Father of English Poetry”. Chaucer explored the development of English language literature against the background of the historic changes in English society, drew on the artistic nourishment of Italian, French and Latin poetry, and insisted on composing in English, establishing the direction of the development of English poetry, opening up a new era of English literature, and laying the foundation for the full prosperity of English literature in the Elizabethan era. Courtly love, as an important tradition of medieval literature, initially originated in Provence and entered England with the spread of French court culture. Inheriting this tradition, Chaucer’s works redefined the connotations of love, marriage and class relations with the help of satire, parody and profound characterization. By analyzing Chaucer’s works such as The Book of the Duchess and Parliament of fowls eng in the early period of his creation, Troilus and Criseyde in the middle period, and The Canterbury Tales in the later period, this article explores how Chaucer reconstructed the manifestations and values of courtly love in the light of the social changes in 14th-century England, especially the elevation of women's status and the mobility of social class, to innovate and criticize the traditional theme of courtly love. The article argues that Chaucer reconstructed the traditional concept of courtly love and comprehensively demonstrated the multiple positions and views on marriage and women’s issues in English society at that time with an open and tolerant attitude, reflecting the progressiveness of his thought and humanistic concern.